FAKTOR-FAKTOR YANG MEMPENGARUHI IMPLEMENTASI PROGRAM BPJS KESEHATAN DI KECAMATAN TANAH JAWA KABUPATEN SIMALUNGUN - Rahayu, Niati; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
BPJS Kesehatan is a program from the government of Indonesia who changed ASKES as caretaker health to the society health assurance by BPJS Kesehatan to the society can help prosperous the society in healthy section. In Kecamatan Tanah Jawa Kabupaten Simalungun within implementation BPJS Kesehatan program still found the society less the understanding about the procedure to get the service, the society less get the information about the process of register as participant and many complaints of society about procedure of payment and get service with online system. This research is to identify what is the factors to influence the implementation BPJS Kesehatan program in Kecamatan Tanah Jawa Kabupaten Simalungun.The writer used Edward III theory in this research. The analyzing data used the descriptive qualitative method. Sourse data consist of primary data is the data get from BPJS Kesehatan side Simalungun regency, meanwhile the secondary data is data based on document from BPJS Kesehatan Kabupaten Simalungun and clinic in Kecamatan Tanah Jawa. Collecting data used observation, interview and documentation. Analyzing data technique is presentation data, draw, and inference.Result of the research refers to know the dominant factors in the implementation BPJS Kesehatan program in Kecamatan Tanah Jawa Kabupaten Simalungun includes the variables are communication. Communications have meaning sense is deliver all information process about BPJS Kesehatan in Kecamatan Tanah Jawa Kabupaten Simalungun with socialization method to the society. Mean of source data in this research is workers, facilities and competence to do good activities in organization and in the field to deliver BPJS Kesehatan program in Kecamatan Tanah Jawa Kabupaten Simalungun. Authorizing signature in this research is attitude and respons the implementer employed showed loyalty to each activities in deliver information,directive and bureaucracy structure. That's mean is structure and relation between unit and function, and operational structure in institution and related instantion.Key Words : Public Policy, Implementation, BPJS Health